SOCIOCULTURAL ASPECT OF MODERN-STIENTIFIC COMMUNICATIONS - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted the philosophical analysis of the informative-communicative systems in the context of culture of informative epoch.